Computerization of Land Records in West Bengal. - Ahuja, Manoj and Singh, A.P (2006)
This article gives an idea of the benefits accruing to landowners by the computerization of land records in West Bengal. Though a lot of work has been done, there still are deficiencies in the system, which need to be addressed so as to make this programme useful at large. Unless the database of land records related information is updated concurrently with a mutation order, the database loses its relevance, as it does not reflect the current reality. Therefore, the mutation process has to be made online along with imparting training to the staff concerned, ensuring proper security mechanisms and providing the necessary infrastructure.